A new species of Plagiognathus (Heteroptera: Miridae) associated with the locally endemic Phlomis leucophracta (Lamiales: Lamiaceae) from Karaman, Turkey - Çerçi, Barış (European Journal of Taxonomy, 2022)
Plagiognathus ozgurkocaki sp. nov. is described based on a long series of specimens from Karaman, Turkey. The new species is remarkable among its congeners in Palearctic Region due to the combination of following characters: remarkably small size, dense and unicolorous pale yellow vestiture, darkened cuneus and yellow first antennal segment with a basal ring and pre-apical dots. The new species is associated with the endemic Phlomis leucophracta P.H.Davis & Hub.-Mor. (Lamiaceae) which makes it unique among all its congeners. Additionally, Plagiognathus bipunctatus albicans (Reuter, 1901) and Plagiognathus marivanensis Linnavuori, 2010 are recorded from Karaman, former constitutes a new record for Turkey.